Bibliometric Analysis of Global Research on Classroom Incivility - Malodia, Luxmi; Butail, Priya Kumari (Gyan Management Journal, 2024)
Purpose- The purpose of this study is bibliometric analysis of  classroom incivility articles published in the journals indexed in  Scopus database between 1996 to 25th May, 2023. Design/Methodology/Approach- In bibliometric analysis, a systematic  review of classroom incivility using Scopus database has been done. Findings- The publishing trend indicated that the analysis in the field  of classroom incivility is in nascent stage. Regarding journals, citation  impact, co-authorship, institutions, and authors in this research topic,  the United States placed first. Classroom incivility has mainly been  associated with nursing field. The most influential journals are Journal  of Nursing Education followed by Nurse Educator, Nurse Education  Today, and Nursing Education Perspectives. And the most popular  keywords are student incivility, social behaviour, incivility and  classroom incivility on the basis of their occurrence.
Keywords: Classroom Incivility; Uncivil Behaviour; Student Incivility; Bibliometric Analysis